Acceptance of the concept of sustainable development: Implications for university teaching - Prodović-Milojković Biljana T. (Univerzitetska Misao, 2023)
Referring to the National Strategy for Sustainable Development (National Strategy for Sustainable Development, 2008) the obligation of all today's generations is to leave enough chances for development to posterity. That is why the task of the modern world is to harmonize its development with the needs of people and nature, all with the aim of preserving the Earth, both for the current generation and for future generations of people to come.The research has an empirical character, which is aimed at determining the attitudes of future pedagogical staff (future educators) on sustainable development. The aim of the author's work is to examine the connection of attitudes towards the goals of sustainable development with the socio-demographic characteristics of the respondents, and especially with gender and different regional and national affiliations. A descriptive method was used in the research. The technique of data collection used in the research is the survey technique, and a questionnaire was used as an instrument to assess attitudes about sustainable development. Citizens' awareness of sustainable development, which includes an understanding of the concept of sustainable development, is below the level of awareness of the contents and goals of sustainable development. The obtained findings indicate insufficient recognizability not only of the content of this concept, but also of the construction of the concept of sustainable development. One of the reasons for such a thing lies primarily in the absence of a holistic view of sustainable development. The authors of the research did not confirm the hypothesis that the more pronounced women's values are in culture, the more certain the acceptance of the concept of sustainable development; although they found a partial explanation in the characteristics of the sample itself and the values of the index. By proving that there are regional differences in the value attitudes of the respondents, the authors confirmed the hypothesis that the more pronounced the regional differences, the more pronounced the differences in the value attitudes of the respondents. Despite the essential ignorance of the concept, with the possible connection to some peripheral elements of sustainable development, the authors emphasize its popularization and promotion. Despite the obvious fatigue and failure of experts who are professionally engaged in education in this field, and especially carried by the fact that there is little research that deals with students' attitudes in the field of education and sustainable development, the author intends to elaborate on this topic. and explore deeper. on them which leads them in the area of utopic literature.